EFFECTS OF CHROMIUM PICOLINATE ON OXIDATIVE STRESS AND HYPERGLYCEMIA IN EXPERIMENTAL TYPE 2 DIABETIC RATS - USLU, HAMİT; ATİLA USLU, GÖZDE (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In this study, we aimed to determine the effects of chromium picolinate (CrPic) on diabetes, one of the most common and fatal diseases in the world, and its associated oxidative damages. Methods: CrPic (100 Î¼g/kg) and metformin (1000 mg/kg) were orally administered for 21 days in rats with nicotinamide + streptozotocin-induced Type 2 diabetes. Results: Significant decreases in fasting blood glucose levels were observed 14 days after initial administration in both CrPic (p<0.01) and metformin (p<0.001) groups compared with a diabetic control group (DC). Malondialdehyde (MDA) levels of all tissues were significantly higher in the DC group than in a normoglycemic control group (p<0.001). MDA levels of the CrPic group significantly decreased in heart (p<0.05) and liver (p<0.01) tissues. Glutathione (GSH) and catalase (CAT) levels in heart, kidney, and liver tissues increased in CrPic group (GSH p<0.001, p<0.05, and p<0.01; CAT p<0.001, p<0.001, and p<0.05, respectively). Superoxide dismutase enzyme levels significantly increased in CrPic group in the liver tissue (p>0.001), but no such changes were observed in heart and kidney tissues (p>0.05). Conclusion: The results obtained from this study indicate that CrPic may be effective in alleviating hyperglycemia and its consequent oxidative damage in experimental Type 2 diabetes.